Associations between serum vitamin D levels and precocious puberty in girls - Hae Sang Lee; You Jin Kim; Young Seok Shim; Hwal Rim Jeong; Eunbyul Kwon; Jin Soon Hwang (Korean Society of Pediatric Endocrinology, 2014)
PurposeVitamin D deficiency has been linked to chronic diseases, such as diabetes mellitus, obesity and autoimmune disease. However, data on the vitamin D status and its association with precocious puberty in girls are limited. We aimed to investigate the association between serum 25-hydroxyvitamin D (25OHD) and precocious puberty in girls.MethodsA total of 60 girls with central precocious puberty (CPP) and 30 control girls were enrolled. Anthropometric measurement and serum level of 25OHD were estimated for all subjects.ResultsThere was a significant difference in the mean serum 25OHD concentration between the precocious puberty group and the control group (17.1±4.5 ng/mL vs. 21.2±5.0 ng/mL, P<0.05). Forty-two of the 60 girls with CPP (70%) had vitamin D deficiency (defined as serum 25OHD<20 ng/mL) and 18 (30%) had vitamin D insufficiency. Of the 30 girls in the control group, vitamin D deficiency was seen in 13 subjects (43.3%), 15 subjects (50%) had vitamin D insufficiency, and 2 subjects (6.7%) had sufficient serum vitamin D (defined as serum 25OHD>30 ng/mL). Vitamin D deficient girls had a significantly higher odds ratio (OR, 3.05; 95% CI, 1.22-7.57, P=0.021).ConclusionThese results showed that vitamin D levels may be associated with precocious puberty. Further studies are required to establish the potential effect of vitamin D status on puberty.